The Motives behind the Skepticism of Conventional Medicine Advocates towards Traditional Persian Medicine: An Expert Opinion - Majid Nimrouzi; Zahra Salehi; Faranak Alembizar (Traditional and Integrative Medicine)
The conflict between conventional medicine and traditional medicine is an issue worldwide. Various factors contribute to this dissent. In our study, we have explained that there are several denunciations about traditional medicine mentioned by proponents of conventional medicine. A search of important databases utilized related keywords to describe this purpose. Furthermore, the main Persian medicine resources were reviewed. Some critiques are because of a knowledge gap between ontology and epistemology of complementary medical approaches and conventional medicine. The other issue is the inadequate self-presentation of traditional medicine modalities to unwrap its obscure points for contemporary paradigm advocates to promote its points of strength. Traditional and conventional medicine share many abilities, but they cannot address all healthcare requirements alone. If we delineate medicine as a distinct system, it is a knowledge-based art for palliating physical and mental pains, and the traditional/conventional classification of medicine and separating these two schools is the first terrible impediment. It is believed by many that personalized medicine improves the management of patients. To achieve medicine's true objective - preserving and restoring health - we should move towards integrative medicine and validate patients' priorities and human values. The objective of this viewpoint is to enhance health awareness in both academia and the public sphere.